2019
DOI: 10.17305/bjbms.2019.4434
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-9 decreases osteosarcoma cell proliferation

Abstract: Osteosarcoma (OS) is the most common primary bone tumor that affects adolescents and young adults. Disruption of microRNA (miRNA) regulation is well established in the pathophysiology of different cancers, including OS. Increased expression of miR-9 in OS positively correlates with the tumor size, clinical stage, and distant metastasis. In the present study, we used two different OS cell lines, MG-63 and Saos-2, as in vitro models. Small interfering RNA against miR-9 and miR-9 mimics were used to study the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…no. SW3015; Beijing Solarbio Science & Technology Co., Ltd.) for 2 h at room temperature, and then visualized with enhanced chemiluminescence substrate (Pierce; Thermo Fisher Scientific, Inc.) as previously described ( 14 , 15 ). GAPDH was used as a reference protein and lamin was used as a reference for nuclear p65.…”
Section: Methodsmentioning
confidence: 99%
“…no. SW3015; Beijing Solarbio Science & Technology Co., Ltd.) for 2 h at room temperature, and then visualized with enhanced chemiluminescence substrate (Pierce; Thermo Fisher Scientific, Inc.) as previously described ( 14 , 15 ). GAPDH was used as a reference protein and lamin was used as a reference for nuclear p65.…”
Section: Methodsmentioning
confidence: 99%
“…In relation to the presence of this miRNA in OS, Xu S. et al have found that miR-9 is upregulated in OS tissues compared to non-cancerous tissues, and that this overexpression can be correlated with the tumor size and the aggressive progression of OS [ 108 ]. Gang W. et al have demonstrated that the inhibition of miR-9 enhances OS cell apoptosis and inhibits their metastatic potential [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maia D. et al have reported that the high expression levels of miR-296-5p mediate drug resistance and is correlated to tumor recurrence in early-stage laryngeal carcinoma [ 115 ]. Yoon A. et al have demonstrated that miR-296-5p is enriched in cancer cells and, by downregulation of the p53-p21 WAF1 pathway, contributes to tumorigenesis [ 109 ]. miR-654-5p has also recently been identified as an oncomir through Ras/MAPK signaling in oral squamous-cell carcinoma [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] In osteosarcoma, inhibition of miR-9 decreases the proliferation of tumor cells by targeting p16. [ 39 , 40 ] In addition, miR-9 was upregulated in spontaneous canine osteosarcoma and promoted the invasion and migration of osteosarcoma cells. [ 41 ] Meanwhile, miR-9 was an oncogene and promoted proliferation of osteosarcoma through targeting Grap2 and cyclin D interacting protein.…”
Section: Discussionmentioning
confidence: 99%